2011
DOI: 10.1128/aem.02858-10
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the SmeAB Multidrug Efflux Pump in Resistance to Plant Antimicrobials and Contribution to Nodulation Competitiveness in Sinorhizobium meliloti

Abstract: The contributions of multicomponent-type multidrug efflux pumps to antimicrobial resistance and nodulation ability in Sinorhizobium meliloti were comprehensively analyzed. Computational searches identified genes in the S. meliloti strain 1021 genome encoding 1 pump from the ATP-binding cassette family, 3 pumps from the major facilitator superfamily, and 10 pumps from the resistance-nodulation-cell division family, and subsequently, these genes were deleted either individually or simultaneously. Antimicrobial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 62 publications
0
53
0
1
Order By: Relevance
“…In particular, the major effect of luteolin on the sensitivity profile of E. meliloti 3001 was an enhanced resistance towards a large set of antimicrobials and toxic compounds. One of the major system conferring multidrug resistance phenotypes in bacteria are efflux pumps (Eda et al 2011). These systems have also been reported to play an important role in the establishment of the symbiosis between rhizobia and leguminous plants (Cosme et al 2008;Eda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the major effect of luteolin on the sensitivity profile of E. meliloti 3001 was an enhanced resistance towards a large set of antimicrobials and toxic compounds. One of the major system conferring multidrug resistance phenotypes in bacteria are efflux pumps (Eda et al 2011). These systems have also been reported to play an important role in the establishment of the symbiosis between rhizobia and leguminous plants (Cosme et al 2008;Eda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In E. meliloti 1021 14 different multidrug resistance efflux pumps (MDR), one pump belonging to the ATP-binding cassette family (ABC), three pumps belonging to the major facilitator superfamily (MFS), and ten pumps belonging to the resistance-nodulation-cell division family (RND), have been detected (Eda et al 2011). Eda et al (2011) hypothesized that the SmeAB RND type pump had a main role in antimicrobial resistance of E. meliloti. Nevertheless, the authors concluded that the 20 chemicals that they tested could have been unable to highlight the contributions of the other pumps (Eda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nod box is the binding site of NodD, a LysR-type regulator, which activates nodulation genes in the presence of flavonoids (33). In a recent comprehensive study of S. meliloti strain 1021, genes encoding efflux systems belonging to different families were analyzed (5). A deletion of smeAB resulted in an increased sensitivity to toxic compounds and to reduced nodulation competitiveness.…”
mentioning
confidence: 99%
“…A deletion of smeAB resulted in an increased sensitivity to toxic compounds and to reduced nodulation competitiveness. The expression of smeAB is regulated by a TetR-type protein (SmeR), which is encoded within the same operon (5). In two strains of Rhizobium leguminosarum bv.…”
mentioning
confidence: 99%